2016 IEEE International Conference on Software Quality, Reliability and Security (QRS) 2016
DOI: 10.1109/qrs.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Android Vulnerabilities

Abstract: Abstract-In widely used mobile operating systems a single vulnerability can threaten the security and privacy of billions of users. Therefore, identifying vulnerabilities and fortifying software systems requires constant attention and effort. However, this is costly and it is almost impossible to analyse an entire code base. Thus, it is necessary to prioritize efforts towards the most likely vulnerable areas. A first step in identifying these areas is to profile vulnerabilities based on previously reported one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Finally, Jimenez et al [15] analyzed 32 vulnerabilities from the CVE database [49] to identify the issues, involved components, code complexity of the patches, and complexity of the code methods/functions involved in the vulnerability.…”
Section: A Malware and Vulnerabilitiesmentioning
confidence: 99%
“…Finally, Jimenez et al [15] analyzed 32 vulnerabilities from the CVE database [49] to identify the issues, involved components, code complexity of the patches, and complexity of the code methods/functions involved in the vulnerability.…”
Section: A Malware and Vulnerabilitiesmentioning
confidence: 99%
“…Other related studies that analysed vulnerabilities and their patches are due to Milenkoski et al [19], Fonseca et al [20] and Jimenez et al [21]. These studies focus on specific kinds of vulnerabilities and their causes.…”
Section: Vulnerability Prediction Modelling (Vpm): Initiated Bymentioning
confidence: 99%
“…Thomas et al [39] have analyzed 102k+ apks to study a CVE reported vulnerability on the JavaScript-to-Java interface of the WebView API. Jimenez et al [107] have attempted to profile 32 CVE vulnerabilities by characterizing the OS components, the issues, the complexity of the associated patches, etc. Linares-Vásquez et al [108] have then presented a larger-scale empirical study on Android OS-related vulnerabilities.…”
Section: Related Workmentioning
confidence: 99%